2001
DOI: 10.1562/0031-8655(2001)0730642cpitpt2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Phenomena in Two-pulse, Two-color Laser Photocoagulation of Cutaneous Blood Vessels¶

Abstract: A novel laser system has been developed to study the effects of multiple laser pulses of differing wavelengths on cutaneous blood vessels in vivo, using the hamster dorsal skin flap preparation and in vitro, using cuvettes of whole or diluted blood. The system permits sequenced irradiation with well‐defined intrapulse spacing at 532 nm, using a long‐pulse frequency‐doubled Nd:YAG laser, and at 1064 nm, using a long‐pulse Nd:YAG laser. Using this system, we have identified a parameter space where two pulses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 27 publications
8
95
0
Order By: Relevance
“…The in vitro generated thermal coagula appear black (negative contrast) in the DFOPS images, meaning that the source light at 548 nm wavelength is absorbed. These findings are in agreement with the spectroscopic data published by Barton et al [25]. …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The in vitro generated thermal coagula appear black (negative contrast) in the DFOPS images, meaning that the source light at 548 nm wavelength is absorbed. These findings are in agreement with the spectroscopic data published by Barton et al [25]. …”
Section: Resultssupporting
confidence: 94%
“…These coagula, consisting of agglutinated thermolysed red blood cells [19,21], either adhere to the vessel wall or embolize following a laser pulse [19,22]. The optical properties of thermal coagula have been spectroscopically determined in vitro [25]. At 550 nm wavelength (approximately equivalent to the wavelength of the DFOPS light source), blood coagula elicit a reduced transmission, increased absorption and scattering coefficients, but no changes in reflectance [25] in comparison to uncoagulated whole blood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombosis begins immediately after the laser insult but may not resolve for weeks [9,[12][13][14]. Most likely, both mechanisms are involved in the great majority of laser leg vein interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of MPT is recommended with use of the 1,064 nm Nd:Yag laser to treat PWS. In addition, Black et al demonstrated increased absorption during coagulation with the 1,064 nm laser associated with the formation of methemoglobin that may lead to ''runaway'' heat deposition and burns, suggesting the safety profile of long pulsed 1,064 nm lasers may be improved by initial treatment with a 532 nm laser followed by a 1,064 nm laser at lower fluences as demonstrated in Case 2 [8,9]. The use of longer wavelengths and higher fluences to treat vascular lesions may be best reserved for laser experts familiar with the complexities of these lesions and devices (Cases 2,3, and 6).…”
Section: Discussionmentioning
confidence: 99%